АНАЛІЗ РЕЖИМІВ РОБОТИ ЕЛЕКТРОПРИВОДА ПІДВІСНОЇ КАНАТНОЇ ДОРОГИ ПРИ ВИКОРИСТАННІ СИСТЕМИ ВЕКТОРНОГО КЕРУВАННЯ - М.В. Печеник; С.О. Бур’ян; Г.Ю. Землянухіна; Д.В. Руднєв (Праці Інституту електродинаміки Національної академії наук України, 2021)
Continuous transport systems, including rope conveyors designed to move people and goods, are subject to very strict safety and energy efficiency requirements. As a rule, suspended cableways in operation have an unregulated electric drive with a smooth start system. Among the ways to meet these requirements is the use of modern regulated electric drives. The electromechanical system with a vector-controlled asynchronous electric motor is considered in the work. Based on the obtained model, within the framework of the MATLAB / Simulink application package, an investigation of the dynamic characteristics of the cableway electric drive was carried out. An analysis of the nature of the distribution of dynamic error in terms of speed and energy losses depending on the load and speed of movement of the rope traction element of the transport system is given. The results presented in the article make it possible to choose rational electric drives for continuous transport systems with rope traction elements. References 4, figures 5, table.